Effect of Performance Expectations, Effort Expectations, Social Influence, and Facilitation Conditions on Behavioral Intentions in Sharia Entrepreneurship - Horas, Erwin; Iskandar, Sultan; Abidin, Zainal; Daryanti, Daryanti (Universitas Alma Ata, 2023)
This study aims to analyse the fowners that influence the implementation of AIS in MSMEs in Makassar City using the UTAUT model. The data used is primary data. The sample collection technique using the purposive sampling method was 75 respondents. Analysis using SEM-SmartPLS. The study's results prove that performance expectancy, effort expectancy, social influence, and facilitating conditions significantly affect behavioural intentions. These results can be a consideration for MSME players in improving the implementation of AIS information technology to develop business strategy and performance